Parent-to-Child Grants and Their Influence on Inheritance Perspectives of Islamic Law and Positive Law - Intan Intan; Jamhir Jamhir; Yusnaidi Kamaruzzaman; Nor Azlina Mohd Noor; Shadi Imad Ali Qaddumi (An-Nisa: Journal of Islamic Family Law, 2026)
Parental grants (hibah) to children are commonly practiced as an expression of affection and as a means of managing family property during one’s lifetime. However, in practice, such grants often give rise to legal issues, particularly when they affect the distribution of inheritance after the parents’ death. This article aims to examine the legal position of hibah from the perspective of Islamic law, the practice of parental grants to children, and the impact of such grants on inheritance according to Islamic law and Indonesian positive law. This study employs a qualitative approach with a normative-juridical method through library research, analyzing the Qur’an, Hadith, Islamic jurisprudential principles, the Compilation of Islamic Law, and relevant legal literature. The findings indicate that hibah in Islamic law is a valid legal transaction as long as it is conducted voluntarily, fairly, and while the grantor is still alive. Parental grants to children are permissible but must uphold the principle of justice to prevent inequality and family disputes. In principle, a valid hibah does not constitute inheritance property. Nevertheless, under certain circumstances such as unjust grants, grants made shortly before death, or grants intended to circumvent inheritance rules hibah may be calculated as part of the inheritance, as stipulated in Article 211 of the Compilation of Islamic Law. Therefore, hibah and inheritance are closely interconnected and must be implemented based on principles of justice and public benefit.